Divergent Evolution of PcF/SCR74 Effectors in Oomycetes Is Associated with Distinct Recognition Patterns in Solanaceous Plants - Xiao Lin (American Society for Microbiology, 2020)
ABSTRACT Plants deploy cell surface receptors known as pattern-recognition receptors (PRRs) that recognize non-self molecules from pathogens and microbes to defend against invaders. PRRs typically recognize microbe-associated molecular patterns (MAMPs) that are usually widely conserved, some even across kingdoms. Here, we report an oomycete-specific family of small secreted cysteine-rich (SCR) proteins that displays divergent patterns of sequence variation in the Irish potato famine pathogen Phytophthora infestans. A subclass that includes the conserved effector PcF from Phytophthora cactorum activates immunity in a wide range of plant species. In contrast, the more diverse SCR74 subclass is specific to P. infestans and tends to trigger immune responses only in a limited number of wild potato genotypes. The SCR74 response was recently mapped to a G-type lectin receptor kinase (G-LecRK) locus in the wild potato Solanum microdontum subsp. gigantophyllum. The G-LecRK locus displays a high diversity in Solanum host species compared to other solanaceous plants. We propose that the diversification of the SCR74 proteins in P. infestans is driven by a fast coevolutionary arms race with cell surface immune receptors in wild potato, which contrasts the presumed slower dynamics between conserved apoplastic effectors and PRRs. Understanding the molecular determinants of plant immune responses to these divergent molecular patterns in oomycetes is expected to contribute to deploying multiple layers of disease resistance in crop plants. IMPORTANCE Immune receptors at the plant cell surface can recognize invading microbes. The perceived microbial molecules are typically widely conserved and therefore the matching surface receptors can detect a broad spectrum of pathogens. Here we describe a family of Phytophthora small extracellular proteins that consists of conserved subfamilies that are widely recognized by solanaceous plants. Remarkably, one subclass of SCR74 proteins is highly diverse, restricted to the late blight pathogen Phytophthora infestans and is specifically detected in wild potato plants. The diversification of this subfamily exhibits signatures of a coevolutionary arms race with surface receptors in potato. Insights into the molecular interaction between these potato-specific receptors and the recognized Phytophthora proteins are expected to contribute to disease resistance breeding in potato.